Two-Chambered Chitosan Nerve Guides With Increased Bendability Support Recovery of Skilled Forelimb Reaching Similar to Autologous Nerve Grafts in the Rat 10 mm Median Nerve Injury and Repair Model - Dietzmeyer, Nina; Förthmann, Maria; Leonhard, Julia; Helmecke, Olaf; Brandenberger, Christina; Freier, Thomas; Haastert-Talini, Kirsten (Frontiers in Cellular Neuroscience, 2019)
Tension-free surgical reconstruction of transected digital nerves in humans is regularly performed using autologous nerve grafts (ANGs) or bioartificial nerve grafts. Nerve grafts with increased bendability are needed to protect regenerating nerves in highly mobile extremity parts. We have recently demonstrated increased bendability and regeneration supporting properties of chitosan nerve guides with a corrugated outer wall (corrCNGs) in the common rat sciatic nerve model (model of low-mobility). Here, we further modified the hollow corrCNGs into two-chambered nerve guides by inserting a perforated longitudinal chitosan-film (corrCNG[F]s) and comprehensively monitored functional recovery in the advanced rat median nerve model. In 16 adult female Lewis rats, we bilaterally reconstructed 10 mm median nerve gaps with either ANGs, standard chitosan nerve guides (CNGs), chitosan-film enhanced CNGs (CNG[F]s), or corrCNG[F]s (n = 8, per group). Over 16 weeks, functional recovery of each forelimb was separately surveyed using the grasping test (reflex-based motor task), the staircase test (skilled forelimb reaching task), and non-invasive electrophysiological recordings from the thenar muscles. Finally, regenerated tissue harvested from the distal part of the nerve grafts was paraffin-embedded and cross-sections were analyzed regarding the number of Neurofilament 200-immunopositive axons and the area of newly formed blood vessels. Nerve tissue harvested distal to the grafts was epon-embedded and semi-thin cross-sections underwent morphometrical analyses (e.g. number of myelinated axons, axon and fiber diameters, and myelin thicknesses).Functional recovery was fastest and most complete in the ANG group (100% recovery rate regarding all parameters), but corrCNG[F]s accelerated the recovery of all functions evaluated in comparison to the other nerve guides investigated. Furthermore, corrCNG[F]s supported recovery of reflex-based grasping (87.5 %) and skilled forelimb reaching (100%) to eventually significantly higher rates than the other nerve guides (grasping test: CNGs: 75%, CNG[F]s: 62.5%; staircase test: CNGs: 66.7%, CNG[F]s: 83.3%). Histological and nerve morphometrical evaluations, in accordance to the functional results, demonstrated best outcome the in ANG group and highest myelin thicknesses in the corrCNG[F] group as compared to the CNG and CNG[F] groups. We thus clearly demonstrate that corrCNG[F]s represent promising innovative nerve grafts for nerve repair in mobile body parts such as digits.